2017
DOI: 10.1016/j.ejvs.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Amputation Rates, Mortality, and Pre-operative Comorbidities in Patients Revascularised for Intermittent Claudication or Critical Limb Ischaemia: A Population Based Study

Abstract: The risk of amputation is particularly high during the first 6 months following revascularisation for CLI. IC patients have a benign course in terms of limb loss. Mortality in both IC and CLI patients is substantial. Revascularised CLI patients have different comorbidities from IC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(73 citation statements)
references
References 18 publications
(25 reference statements)
4
67
1
1
Order By: Relevance
“…Baubeta Fridh and co-workers analysed mortality and amputation rates during 3 years in a heterogeneous group of PAD patients in Swedvasc having undergone either open or endovascular surgery for CLTI or IC caused by supra- or infrainguinal disease. 19 Mortality in the IC group was 3.4% after 1 year and 12.0% after 3 years. Their 1 year mortality rate is comparable to ours despite our more narrow inclusion criteria, whereas the 5 year mortality in our study cannot be directly compared with their figures due to their shorter follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Baubeta Fridh and co-workers analysed mortality and amputation rates during 3 years in a heterogeneous group of PAD patients in Swedvasc having undergone either open or endovascular surgery for CLTI or IC caused by supra- or infrainguinal disease. 19 Mortality in the IC group was 3.4% after 1 year and 12.0% after 3 years. Their 1 year mortality rate is comparable to ours despite our more narrow inclusion criteria, whereas the 5 year mortality in our study cannot be directly compared with their figures due to their shorter follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Endovascular surgery, a minimally invasive approach, is mostly conducted under local anaesthesia in an angio suite. A majority of the procedures performed for IC in Sweden are undertaken via the endovascular route 2 . The approach is percutaneous, and by using the Seldinger technique an introducer is inserted into the vessel either with or without ultrasound guidance.…”
Section: 2b Invasive Treatment: General Considerationsmentioning
confidence: 99%
“…In open surgery, the arteries explored are fully visible in the operational field by incision of the skin and by dissecting the target arteries free from the surrounding tissues. A minority of the IC procedures are performed by open surgery 2 .…”
Section: 2b Invasive Treatment: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, amputation risk is inherently increased in diabetes, and a history of DFD and amputation are risk factors for CV events, including re-amputation, and poorer prognosis [ 15 , 16 ]. Results of a population-based cohort study showed that the risk of amputation was particularly high during the first 6 months following revascularization for critical limb ischemia [ 17 ]. Actually, a history of amputation and DFD were also strong and independent risk factors for amputation in the CANVAS program [ 3 ].…”
mentioning
confidence: 99%